Response surface methodology (RSM) for optimization of gelatin extraction from pangasius fish skin and its utilization for hard capsules - Mala Nurilmala; Diah Sriwahyuni; Roni Nugraha; Via Ridzna Kartika; Noviyan Darmawan; Erin Apriliani Wulandari Putri; Agy Wirabudi Pranata; Yoshihiro Ochiai (Arabian Journal of Chemistry, 2023)
This study was aimed to investigate the use of the response surface methodology (RSM) to improve the extraction process of pangasius Pangasianodon hypopthalmus fish skin gelatin. RSM was conducted based on central composite design (CCD) consisting of the two factors, namely, citric acid concentration and extraction time. The yield, moisture content, ash content, pH, viscosity, and setting point were all positively correlated with citric acid concentration, whereas the extraction duration influenced the yield, gel strength, moisture content, and setting point. The combination of these two factors improved the physicochemical properties of the final gelatin preparation. The optimized extraction process was found at the citric acid concentration of 0.3 % and the extraction time of 8 h, producing the gelatin of the quality within the standard GMIA. The gelatin resulted from the optimized processing condition was used as a raw material for hard capsules. The characteristics of the capsules produced were in accordance with those of the commercially available hard capsules.